The World Bank's Approach to Grievance Redress in Projects - World Bank (Washington, DC, 2014)
The World Bank is committed to enhancing opportunities for grievance redress, collaborative problem solving, and alternative dispute resolution on the projects it supports. Grievance redress mechanisms (GRMs) can be an effective tool for early identification, assessment, and resolution of complaints on projects. The World Bank Executive Board and senior management are supporting more effective approaches to problem solving to help strengthen the Bank's performance and development outcomes. This note presents the World Bank s recommended approach to strengthening grievance capacity in Bank-supported projects. The approach presents three interlinked steps: (i) a risk-based assessment of potential grievances, disputes, or conflicts that may arise during project preparation and implementation; (ii) identification of the client s existing capacity for grievance redress; and (iii) an action plan that identifies priority areas for strengthening grievance capacity, or if necessary, establishing new mechanisms at the project level.